Nonselective beta‐blockers are associated with a lower risk of hepatocellular carcinoma among cirrhotic patients in the United States. Issue 4 (5th July 2021) - Wijarnpreecha, Karn; Li, Fang; Xiang, Yang; Xu, Xun; Zhu, Cong; Maroufy, Vahed; Wang, Qing; Tao, Wei; Dang, Yifang; Pham, Huy Anh; Zhou, Yujia; Li, Jianfu; et al.
Summary: Background: Previous studies have demonstrated an association between nonselective beta‐blockers (NSBBs) and lower risk of hepatocellular carcinoma (HCC) in cirrhosis. However, there has been no population‐based study investigating the risk of HCC among cirrhotic patients treated using carvedilol. Aims: To determine the risk of HCC among cirrhotic patients with NSBBs including carvedilol. Methods: This retrospective cohort study utilised the Cerner Health Facts database in the United States from 2000 to 2017. Kaplan‐Meier estimate, Cox proportional hazards regression, and propensity score matching (PSM) were used to test the HCC risk among the carvedilol, nadolol, and propranolol groups compared with no beta‐blocker group. Results: The final cohort comprised 107 428 eligible patients. The 100‐month cumulative HCC incidence of NSBBs was significantly lower than the no beta‐blocker group (carvedilol (11.24%) vs no beta‐blocker (15.69%), nadolol (27.55%) vs no beta‐blocker (32.11%), and propranolol (26.17%) vs no beta‐blocker (28.84%) ( P values < 0.0001). NSBBs were associated with a significantly lower risk of HCC (Hazard ratio: carvedilol 0.61 (95% CI 0.51‐0.73), nadolol 0.74 (95% CI 0.63‐0.87), propranolol 0.75 (95% CI 0.66‐0.84) after PSM in the multivariate cox analysis. In subgroup analysis, NSBBs reduced the risk of HCC in cirrhosis with complications and non‐alcoholic cirrhosis. Conclusions: NSBBs, including carvedilol, were associated with a significantly decreased risk of HCC in patients with cirrhosis when compared with no beta‐blocker regardless of complications status. Future randomised‐controlled studies comparing the incidence of HCC among NSBBs should elucidate which NSBB would be the best option to prevent HCC in cirrhosis. Abstract : From the population‐based retrospective cohort study, our novel findings include: (a) The 100‐month cumulative HCC incidence of NSBBs groups were significantly lower than the no beta‐blocker group. (b) NSBBs use was associated with a significant lower HCC risk in the multivariate cox analysis as well as subgroup analyses.